2019
DOI: 10.6061/clinics/2019/e836
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hormonal assessment of adolescent and young adult women with prior premature adrenarche

Abstract: OBJECTIVE: Follow-up studies of girls with premature adrenarche have reported the development of polycystic ovary syndrome, insulin resistance, and dyslipidemia and a propensity to cardiovascular disease. The aim of this study was to analyze the presence of these conditions in patients previously treated at the Universidade Federal do Triângulo Mineiro. METHODS: A total of 130 medical records reported premature adrenarche. One hundred and twenty-two patients were invite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
4
7
0
1
Order By: Relevance
“…In addition, the adult height SDS was within normal values according to Spanish references. Despite differences in inclusion criteria and protocol design, our data are consistent with previous reports ( 11 , 12 , 24 – 27 ). Ibañez et al.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, the adult height SDS was within normal values according to Spanish references. Despite differences in inclusion criteria and protocol design, our data are consistent with previous reports ( 11 , 12 , 24 – 27 ). Ibañez et al.…”
Section: Discussionsupporting
confidence: 91%
“…As reflected in Table 3 , our cohort has a mean age of onset of puberty and menarche similar to that reported by previous publications of girls with premature adrenarche ( 11 , 12 , 24 – 27 ). In 2008, Marco-Hernández et al.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“… 20 , 21 However, studies have shown that girls with BPA develop metabolic syndrome or polycystic ovarian syndrome in adulthood more frequently. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%